ANALISIS ESTETIKA PADA POSTER FILM ‘THE BIG 4’ DENGAN PENDEKATAN FORMALISTIK, EKSPRESIFISTIK, DAN INSTRUMENTALISTIK - justian, repi; Maretita, Alisa (CREATIVA SCIENTIA, 2025)
The process of extracting information in the current era of digitalization is very easy to access, one of which is access to information on the latest and old films for the public to watch and see. One information medium that is easily accessible digitally is posters.  Posters are a means of information media in terms of advertising media, such as the film The Big 4 by Timo Tjahjanto. Film posters have a very important role in the process of promoting a film. The aim of this research is to identify the visual characteristics of the poster that is made so that it can describe the contents of the entire film and the elements used to make this film interesting to watch just by looking at the poster presented. The research method used in this research is a qualitative descriptive method. This qualitative descriptive method only relies on poster visuals regarding color, layout, typography, photography and illustrations. The theoretical approaches used in this research are formalistic, expressive and instrumentalistic from design principles. The research results show that the use of color, layout, typography, photography and illustrations used in posters really influence the audience because it makes it easier for them to recall the contents of the film just by looking at the poster. The poster designed also looks simple and to the point in conveying the content of the film that will be shown. The elements included successfully convey the genre and theme of the film.